AN ANALYSIS TOWARD FANBOY’S SELF-DISCLOSURE - Salmaa Dwi Riyani; Winda Primasari (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
This study aims to provide an overview toward fanboys’ self-disclosure. This study uses a qualitative research method with a case study approach. The present research uses a descriptive qualitative approach. Besides interviewing four informants, the researchers describe the forms of self-disclosure they show in social media such as Instagram and WhatsApp status. The results of the present study shows that by becoming K-Pop fans, teenage boys feel happy doing fanboying activities. The informants reveal their identities as fanboys and develop their thoughts and feelings liking the BTS boyband on social media. By posting on social media, these teenage boys say that they feel better and people do not think that being a fanboy is deviant.